2021
DOI: 10.3389/fonc.2020.556575
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Postoperative Adjuvant Radiotherapy in Atypical Meningioma Patients After Gross Total Resection: A Meta-Analysis Study

Abstract: BackgroundIt still remains unclear whether patients with atypical meningioma (AM) could benefit from postoperative adjuvant radiotherapy (PORT) after gross-total resection (GTR).ObjectiveExploring the effectiveness of PORT on AM patients after GTR.MethodsLiteratures on PubMed, Embase, Web of science, and Scopus databases published between January 2000 and January 2019 were searched. After the selection based on the certain exclusion criteria, the Newcastle-Ottawa evaluation scale was used to evaluate the quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…In contrast, patients in our cohort did not receive routine RT after surgery for a grade 2 or 3 meningioma. Time to recurrence was shorter and tumor control worse in our patients than in patients who received RT after surgery in the published literature [ 38 , 39 ]. However, long-term follow-ups typically show that meningiomas recur despite RT, indicating that the benefit is the delay of recurrence rather than the cure.…”
Section: Part 1 Long-term Follow-up and Outcomementioning
confidence: 82%
See 1 more Smart Citation
“…In contrast, patients in our cohort did not receive routine RT after surgery for a grade 2 or 3 meningioma. Time to recurrence was shorter and tumor control worse in our patients than in patients who received RT after surgery in the published literature [ 38 , 39 ]. However, long-term follow-ups typically show that meningiomas recur despite RT, indicating that the benefit is the delay of recurrence rather than the cure.…”
Section: Part 1 Long-term Follow-up and Outcomementioning
confidence: 82%
“…SRS is typically recommended for small residual or recurrent tumors [ 24 ]. Several studies have shown that RT improves PFS but not OS [ 38 , 39 ]. Rogers et al [ 12 ] reported a 59% 3-year PFS and 69% local control after RT for high-risk meningiomas, indicating that RT may be beneficial in these patients.…”
Section: Part 1 Long-term Follow-up and Outcomementioning
confidence: 99%
“…Each included study was evaluated and assigned a total score ranging from zero to nine. Studies with ve or more points were considered high quality [36,37].…”
Section: Synthesis and Assessment Of Literaturementioning
confidence: 99%
“…The effectiveness of postoperative adjuvant RT in patients with atypical meningiomas has been evaluated in several retrospective series [ 5 , 35 , 36 , 38 41 , 43 46 , 48 53 , 56 , 59 , 61 ] (Table 1 ). A recent meta-analysis of 17 studies published between January 200 and January 2019 and including 2008 patients who have undergone gross total resection of atypical meningiomas showed a significant improvement in 5-year local control and progression-free survival rates for those receiving adjuvant RT [ 9 ]. Local control, progression-free survival, and overall survival rates were 82.2%, 84.1%, and 79%, respectively, for patients treated with adjuvant RT, and 71%, 71.9%, and 81.5%, respectively, for those not receiving the treatment.…”
Section: Radiation Therapy Outcomementioning
confidence: 99%
“…Beyond surgery, external beam radiation therapy (RT) has been usually recommended to increase local control after resection of grade 2 and 3 tumors [ 6 ]. The evidence supporting this treatment recommendation largely comes from systematic reviews including retrospective series [ 7 9 ] and two recent nonrandomized observational prospective trials conducted by the Radiation Therapy Oncology Group (RTOG 0539) [ 4 , 10 ] and the European Organisation for Research and Treatment of Cancer (EORTC 22042) [ 11 ]; however, several issues remains a matter of debate, including the timing of the treatment (early versus delayed postoperative RT), the optimal radiation technique, and types of radiation dose and fractionation. One of the most controversial topics is the superiority of early adjuvant RT over observation in reducing the risk of tumor recurrence after gross total surgical resection in patients with atypical meningiomas.…”
Section: Introductionmentioning
confidence: 99%